The development of a novel grip motion analysis technique using the Dartfish movement analysis software to evaluate hand movements during activities of daily living. (November 2020) - Holland, Sara; Straatman, Lauren; MacDermid, Joy; Sinden, Kathryn; Lalone, Emily
Highlights: Grip ROM defects in people with hand arthritis were simply measured and evaluated. The Dartfish Software provided a non-invasive evaluation of the hands small movement patterns. People with hand arthritis had a 17% reduction in flexion and 13% in extension. The Dartfish Software was a reliable measurement technique. The Grip Configuration Model could be used to gauge the progression of hand arthritis. Abstract: Individuals with hand osteoarthritis (OA) have impairments in grip strength and range of motion (ROM). Obtaining quantitative joint angle measures of the hand is difficult. Without a complete understanding of the kinematics of the hand, the assessment of hand OA when performing activities of daily living (ADL) and recreational activities is not fully understood. The objectives of this study were to establish a simple measurement technique (Grip Configuration Model) describing an individual's grip ROM using the Dartfish Movement Analysis Software, and compare the joint angle measures during maximum flexion/extension and five ADL in people with/without hand OA. Forty participants (20 without hand OA, 20 with hand OA) thumb CMC and MCP, and index MCP and PIP joint angles were evaluated for each activity using the Dartfish Software and Grip Configuration Model. Significant limitations of 17.2% ( p  < 0.001) and 12.7% ( p  = 0.01) were seen in the group with hand OA for maximum flexion/extension, respectively. The spray bottle task demonstrated a significant difference of 14.7% ( p  = 0.001) between the two test groups. Measurements using the Dartfish Software were compared against a manual goniometer and electromagnetic tracking system. This study demonstrated the weakened ROM in individuals with hand OA is translated to ADL and how the Grip Configuration Model simplifies the evaluation of how people grasp objects.